การพัฒนาทักษะด้านการพูดภาษาอังกฤษของนักศึกษาโดยใช้กระบวนการวิจัยเป็นฐาน กรณีศึกษา ชุมชนแหล่งท่องเที่ยวเชิงวัฒนธรรม บ้านปะอาว จังหวัดอุบลราชธานี - ดวนใหญ่, สุภาพร; สายดวง, พิกุล (วารสาร ศึกษาศาสตร์ มมร; Vol 6 No 2 (2018): วารสารศึกษาศาสตร์ มมร ปีที่ 6 ฉบับที่ 2 (กรกฎาคม - ธันวาคม 2561), 2018)
การวิจัยครั้งนี้เป็นการวิจัยเชิงปริมาณและเชิงคุณภาพ โดยมีวัตถุประสงค์เพื่อ 1) พัฒนาทักษะการพูดภาษาอังกฤษ ของนักศึกษามหาวิทยาลัยราชภัฏอุบลราชธานี 2) ฝึกทักษะนักศึกษาในการนำกระบวนวิจัยไปใช้ในการค้นคว้าหาความรู้ด้วยตนเองและ 3) ส่งเสริมนักศึกษาในการมีส่วนร่วมอนุรักษ์และเผยแพร่ชุมชนแหล่งท่องเที่ยวเชิงวัฒนธรรม บ้านปะอาว โดยมีกลุ่มตัวอย่างเป็นนักศึกษาสาขาวิชาภาษาอังกฤษ ชั้นปีที่ 4 มหาวิทยาลัยราชภัฏอุบลราชธานี ปีการศึกษา 2559 ที่เรียนวิชาการศึกษาอิสระ จำนวน 20 คน ซึ่งได้มาโดยการเลือกแบบเจาะจง เครื่องมือที่ใช้ในการวิจัยประกอบด้วย แผนการจัดกิจกรรมการเรียนรู้รายวิชาการศึกษาอิสระ จำนวน 11 แผน แบบประเมินทักษะการพูดภาษาอังกฤษ และแบบบันทึกการสังเกตขณะปฏิบัติการวิจัย วิเคราะห์ข้อมูลเชิงปริมาณโดยการหาค่าเฉลี่ยร้อยละ และเชิงคุณภาพโดยการวิเคราะห์เนื้อหา โดยการจำแนกถ้อยคำ หรือข้อความที่กลุ่มตัวอย่างแสดงความคิดเห็น แล้วนำมาตีความ สังเคราะห์ และวิเคราะห์ด้วยหลักแห่งเหตุผล สร้างข้อสรุปแบบอุปนัย อภิปรายถึงข้อเท็จจริงที่ค้นพบตามสภาพการณ์ ปรากฏการณ์ ความสัมพันธ์ และประเด็นสำคัญ เพื่อตอบคำถามการศึกษา             ผลการวิจัย พบว่า 1) ทักษะการพูดภาษาอังกฤษ ของนักศึกษา เมื่อพิจารณาคะแนนเฉลี่ยของการนำเสนอผลการวิจัยระหว่างบทที่ 1-3 (ครั้งที่ 1) และบทที่ 4-5 (ครั้งที่ 2) มีคะแนนเฉลี่ยเพิ่มขึ้น คิดเป็นร้อยละ 9.20 2) ผลการสังเกตพฤติกรรมขณะปฏิบัติการวิจัยของนักศึกษาระหว่าง บทที่ 1-3 (ครั้งที่ 1) ครั้งที่ 1 และบทที่ 4-5 (ครั้งที่ 2)  มีคะแนนเฉลี่ยเพิ่มขึ้น คิดเป็นร้อยละ 7.81 3) นักศึกษามีส่วนร่วมอนุรักษ์และเผยแพร่ชุมชนแหล่งท่องเที่ยวเชิงวัฒนธรรม บ้านปะอาว โดยการจัดทำวีดิทัศน์และฐานข้อมูลเว็บไซต์แหล่งท่องเที่ยวเชิงวัฒนธรรมหัตถกรรมเครื่องทองเหลืองบ้านปะอาวทั้งภาษาไทยและภาษาอังกฤษ             This research was both quantitative and qualitative with the following aims 1) to develop the speaking skills of Ubon Ratchathani Rajabhat University students 2) to practice students to adopt research methodology to use with their self-learning and 3) to promote the students’ participation in the conservation and publicity of cultural community tourist attractions in Ban Pa Ao. The subjects of the study were 20 fourth year Ubon Ratchathani Rajabhat University, English major students, who enrolled in an Independent Study course in the academic year 2016. A purposive sampling method was used for selecting the subjects. The instruments were 11 Independent Study course lesson plans, an English speaking evaluation form, and a participant observation form. The quantitative data was analyzed to find the mean and percentage, and the qualitative data was analyzed by using content analysis by identifying words or messages from participants’ opinions and interpreting, synthesizing, and analyzing logically. Analytic induction was used for conclusion. Discussion was made based on facts from the situations, incidents, relationships, and significant issues to answer research questions.               The results showed that 1) students’ speaking skills operationalized as the students’ speaking mean score of unit 1-3 research presentation (first presentation) compared to unit 4-5 research presentation (second presentation) increased by 9.20 %. 2) The results of the class observation of unit 1-3 (first phase) compared to unit 4-5 (second phase) increased by 7.81 %. 3) The Students participated more in conservations and publicized cultural tourist attraction, in Ban Pa Ao, by creating a Thai and English video clip and database website of the handmade brass crafts of the cultural community tourist attraction, Ban Pa Ao.